Intralesional interleukin‐2: A novel option to maximize response to systemic immune checkpoint therapy in loco‐regional metastatic melanoma. Issue 3 (29th April 2019) - Langan, Ewan A.; Kümpers, Christiane; Graetz, Victoria; Perner, Sven; Zillikens, Detlef; Terheyden, Patrick
Abstract: The management of metastatic melanoma has been transformed by the development of immune checkpoint inhibitors. However, disease control in patients with extensive locoregional metastases remains a significant challenge. In this context, intralesional interleukin 2 (IL‐2) presents a useful therapeutic option to maximize intratumoural drug concentration and minimize systemic toxicity. The utility of combined intralesional IL‐2 and systemic immune checkpoint therapy, particularly in loco‐regional disease, is unknown. We report the clinical and cellular effects of combined anti‐programmed death‐1 blockade and intralesional IL‐2 therapy in two patients with loco‐regional metastatic melanoma. Combined intralesional and systemic therapy induced a lasting resolution of the injected skin tumors; maintained for up to 2 years. This impressive response was associated with increased PD‐L1 expression and CD8 T cell infiltration. To our knowledge, this is the first report that raises the possibility of a synergistic effect between intralesional IL‐2 and systemic checkpoint inhibition. The lasting remission of injected metastases may be in part due to an altered tumor microenvironment; characterized by increased PD‐L1 expression and increased CD8 T cell infiltration. If this interesting and novel preliminary observation is confirmed in larger studies, combined local and systemic immunotherapy could highlight a novel treatment strategy for extensive loco‐regional disease.